2008
DOI: 10.1889/1.2835025
|View full text |Cite
|
Sign up to set email alerts
|

Flexible active‐matrix OLED displays: Challenges and progress

Abstract: Abstract— Organic light‐emitting‐device (OLED) devices are very promising candidates for flexible‐display applications because of their organic thin‐film configuration and excellent optical and video performance. Recent progress of flexible‐OLED technologies for high‐performance full‐color active‐matrix OLED (AMOLED) displays will be presented and future challenges will be discussed. Specific focus is placed on technology components, including high‐efficiency phosphorescent OLED technology, substrates and back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Organic semiconductors developed for OLEDs and OPDs have been primarily applied to display and photovoltaic technologies 17,18 . This is due to their potential for large-area roll-to-roll manufacturing at large volumes, which is enabled by solution processing and the use of flexible substrates 19 .…”
mentioning
confidence: 99%
“…Organic semiconductors developed for OLEDs and OPDs have been primarily applied to display and photovoltaic technologies 17,18 . This is due to their potential for large-area roll-to-roll manufacturing at large volumes, which is enabled by solution processing and the use of flexible substrates 19 .…”
mentioning
confidence: 99%
“…We found that the device has no significant degradation of the image under bending. [18,19,20] These results indicate that flexible PLED on CPI substrate has a high potential for its application as flexible display.…”
Section: Resultsmentioning
confidence: 94%
“…To further protect and ruggedize a flexible OLED display, an adhesive material and process has also been developed to laminate a protective anti-reflective hardcoat film over the thin-film-encapsulated flexible OLED, 8 as shown in Fig. 5.…”
Section: Conformal Packagingmentioning
confidence: 99%